Electrical characterization of AMS aH18 HV-CMOS after neutrons and protons irradiation - Sultan, D. M. S.; Schöning, André; Herkert, Adrian; Augustin, Heiko (Journal of Instrumentation, 2019)
In view of the tracking detector application to the ATLAS High Luminosity LHC (HL-LHC) upgrade, we have developed a new generation of High Voltage CMOS (HV-CMOS) monolithic pixel-sensor prototypes featuring the AMS aH18 (180 nm) commercial CMOS technology. By fully integrating both analog and digital readout-circuitry on the same particle-detecting substrate, current challenges of hybrid sensor technologies, i.e., larger readout input-capacitance, lower production-yield, and higher production and integration cost, can be downscaled. The large electrode design using high-resistivity substrates actively helps to mitigate the charge-trapping effects, making these chips radiation hard. The surface and bulk damage induced in high irradiation environment change the effective doping concentration of the device, which modulates high electric fields as the reverse-bias voltage increases. This effect can cause high leakage current and premature electrical breakdown, driven by impact ionization. In order to assess the characteristics of heavily irradiated samples, we have carried out dedicated campaigns on ATLASPix1 chips that included irradiations of neutrons and protons, made at different facilities. Here, we report on the electrical characterization of the irradiated samples at different ambient conditions, also in comparison to their pre-irradiation properties. Results demonstrate that hadron irradiated devices can be safely operated at a voltage high enough to allow for high efficiency, up to the fluence of 2× 1015 neq/cm2, beyond the radiation levels (TID and NIEL) expected in the outermost pixel layers of the new ATLAS tracker for HL-LHC.
Gesehen am 10.03.2020